2012
DOI: 10.1152/jn.00923.2010
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchy of direction-tuned motion adaptation in human visual cortex

Abstract: Lee HA, Lee SH. Hierarchy of direction-tuned motion adaptation in human visual cortex. J Neurophysiol 107: 2163-2184, 2012. First published January 4, 2012 doi:10.1152/jn.00923.2010.-Prolonged exposure to a single direction of motion alters perception of subsequent static or dynamic stimuli and induces substantial changes in behaviors of motion-sensitive neurons, but the origin of neural adaptation and neural correlates of perceptual consequences of motion adaptation in human brain remain unclear. Using funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 91 publications
(114 reference statements)
0
16
0
Order By: Relevance
“…In a coherent motion stimulus, the local motion direction of individual dots is the same as the global direction of the stimulus. The specialization of V3A in coherent motion processing might be a result of its greater capacity to process local motion signals than MT+, which is underpinned by its relatively small receptive field sizes and narrow tuning curves for motion direction (27,28). In a noisy motion stimulus, only some dots move in the global direction, whereas others move in random directions and can be treated as noise.…”
Section: Discussionmentioning
confidence: 99%
“…In a coherent motion stimulus, the local motion direction of individual dots is the same as the global direction of the stimulus. The specialization of V3A in coherent motion processing might be a result of its greater capacity to process local motion signals than MT+, which is underpinned by its relatively small receptive field sizes and narrow tuning curves for motion direction (27,28). In a noisy motion stimulus, only some dots move in the global direction, whereas others move in random directions and can be treated as noise.…”
Section: Discussionmentioning
confidence: 99%
“…(2) These areas may contain perceivedspeed-selective neurons in smaller proportion than hMTϩ does. Although the monkey area V1 contains neurons showing direction-dependent surround suppression (Jones et al, 2001), the proportion of direction-selective neurons is generally smaller than that found in area MT (Hawken et al, 1988), and the difference in the proportion of neurons might affect the results, as argued in a recent report (Lee and Lee, 2012). However, neuroimaging studies have also demonstrated a greater directionselective responses in V3A (Nishida et al, 2003;Ashida et al, 2007) or even in V1 (Huk et al, 2001;Kamitani and Tong, 2006;Ales and Norcia, 2009); hence; limited cellular proportion may not limit the BOLD signal change.…”
Section: Activity In Other Visual Areasmentioning
confidence: 94%
“…Murray, Olman, Kersten, 2006; Larsson, Landy, & Heeger, 2006). Three lines of evidence suggest that the bulk of extrastriate adaptation to such simple features originates in V1: first, the tuning of motion adaptation in area MT is very similar to that in V1 (Lee & Lee, 2012), and contrast adaptation in V2 and V3 (but not V4) is nearly identical to that in V1 (Gardner et al, 2005); second, the spatial specificity (i.e. tuning) of direction-selective and orientation-selective adaptation in extrastriate areas is identical to that in V1 (Larsson & Harrison 2015); third, adaptation to motion induces strong motion-selective responses in areas that normally lack such selectivity, including area V4 (Larsson & Harrison 2015).…”
Section: What Are the Concerns With Fmri Adaptation?mentioning
confidence: 99%
“…Specifically, the ability of fMRI to simultaneously measure correlates of neural activity across multiple brain regions means that fMRI adaptation is particularly suitable to addressing questions about how adaptation cascades across sensory hierarchies, particularly in brain areas that are not easily accessible with direct neuronal recordings or invasive neuronal population measurements, such as LFP or optical imaging. In this context, methods to trace the inheritance of adaptation effects using spatially selective adaptation (Larsson & Harrison, 2015) hold promise, as well as techniques that measure the tuning of adaptation across cortical areas (Lee & Lee, 2012). A full understanding of the relationship between single-neuron and population measurements of adaptation effects will also require concerted effort to conduct parallel and directly comparable experiments with fMRI and direct neuronal recordings.…”
Section: What Can Be Done?mentioning
confidence: 99%